Pulse Chase of Suspension Cells - Wong, Lai-Yee (Bio Protoc, 2014)
Pulse-chase method is a powerful technique used to follow the dynamics of proteins over a period of time. The expression level, processing, transport, secretion or half-life of proteins can be tracked by metabolically labeling the cells, such as with radiolabeled amino acids (pulse step). This protocol describes the condition used to study the folding and disulfide bond formation of immunoglobulin in suspension cells. With some minor modifications, this protocol can be adapted to study the degradation rate or the secretion of target proteins.